The Pastoral Epistles Through the Centuries - Twomey, Jat (Chichester WILEY-BLACKWELL, 2009)
Drawing on scholarly insights and a comprehensive array of texts from the entirety of Christian tradition, The Pastoral Epistles Through the Centuries explores the rich legacy of the Pastorals as it has unfolded over the centuries.:.; Explores the impor
Keywords: Bible. -- Pastoral Epistles -- Commentaries. Bible. -- Pastoral Epistles